The Moderating Role of Board Gender Diversity on the Relationship Between Audit Committee Financial Expertise and Corporate Green Innovation: Evidence from GCC Countries - Samour, Ahmed (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study investigates the influence of board gender diversity and audit committee financial expertise (ACE) on corporate green innovation. Unlike previous research, it emphasizes the moderating role of board gender diversity in the relationship between ACE and green innovation within Gulf Cooperation Council (GCC) countries. Analyzing data from listed GCC firms from 2015 to 2024 and employing various robust methods, the study finds that ACE positively impacts green innovation. Additionally, results indicate that board gender diversity enhances sustainable practices by promoting green innovation. The research further reveals that gender diversity on boards strengthens the link between ACE and green innovation, highlighting its moderating effect. These findings underscore the significance of board gender diversity and ACE in fostering sustainability by establishing effective internal controls, which can mitigate business risks and support green innovation adoption. The results are consistent across different estimation techniques, including System GMM, lagged models, and Blau's Index. This research provides valuable insights for policymakers and corporate leaders aiming to align governance structures with sustainability objectives.